2019
DOI: 10.1111/sji.12807
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes in tumour and transplant immune regulation

Abstract: Exosomes are a potent means for intercellular communication. However, exosomes have received intensive research focus in immunobiology only relatively recently.Because they transport proteins, lipids and genetic material between cells, they are especially suited to amplify their parental cell's message and overcome the physical constraints of cell-to-cell contact, that is exosome release gives cells the ability to alter distant, non-contiguous cells. As progress is made in this field, it has become increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 87 publications
0
18
0
1
Order By: Relevance
“…Other secreted proteins involved in the regulation of antitumor immunity in the TME, such as vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), C–C motif chemokine ligand 2 (CCL2), and C–C motif ligand 5 (CCL5), were also found in EC [40, 43, 44]. In addition to soluble secreted proteins, exosomes derived from tumor cells or stromal cells also play critical roles in the inhibition of antitumor immunity [45]. It has been shown that EC-derived exosomes have the ability to induce regulatory B cells, which produce TGF-β and thus suppress the proliferation and activities of CD8 + T cells [46].…”
Section: Regulation Of Antitumor Immunity In Ecmentioning
confidence: 99%
“…Other secreted proteins involved in the regulation of antitumor immunity in the TME, such as vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), C–C motif chemokine ligand 2 (CCL2), and C–C motif ligand 5 (CCL5), were also found in EC [40, 43, 44]. In addition to soluble secreted proteins, exosomes derived from tumor cells or stromal cells also play critical roles in the inhibition of antitumor immunity [45]. It has been shown that EC-derived exosomes have the ability to induce regulatory B cells, which produce TGF-β and thus suppress the proliferation and activities of CD8 + T cells [46].…”
Section: Regulation Of Antitumor Immunity In Ecmentioning
confidence: 99%
“…Exosomes play an important role in immune regulation, eliciting both positive and negative “unwanted” immune responses, including tolerance and evasion. 160 162 Individually, exosomes can act as immunoregulating agents by modulating immune activation, antigen presentation, suppression, and surveillance. 163 166 The exact mechanisms for many of these actions are not entirely understood.…”
Section: Preclinical Research Developmentsmentioning
confidence: 99%
“…Молекулярный «груз» экзосом представляет особый интерес, поскольку он обогащен компонентами, полученными из плазматической мембраны родительской клетки. Везикулярное содержимое экзосом включает нуклеиновые кислоты, ферменты, цитокины, а также различные растворимые компоненты, которые отражают цитоплазматическое содержание родительской клетки [4,5]. Экзосомные мембраны обогащены тетраспанинами, которые организованы в обогащенные тетраспанином мембранные домены (TEMs) и, как полагают, играют ключевую роль в биогенезе экзосом [6].…”
Section: краткие сообщения введениеunclassified